O que pode o teatro como poética do acontecimento : cartografias de desejos e uma ode à desobediência - Leite, Daniela Correa (2019)
Is it possible to weave a poetics of the relation between artistic languages, concepts and affections? From this initial question was built an affective cartography that allowed to inhabit territories of artistic creation. The thesis was composed with a look at the transit of affections between two scenic events: OraMortem and in-Proper for Dinosaurs. Transits that suggested many possibilities of reading in the creation of a poetic that receives the event like compass, to find the tracks of the composition of the writing, like the notions of creolization, by Eduard Glissant; auto-profession, by Serge Doubrovsk; desire, by Gilles Deleuze. The intertwining of concepts and artistic experiences led me to a poetics of the relationship that seeks the event, something that suggests an opening to other possibilities of existence and, therefore, seeks its insertion in time and space.